PENDIDIKAN ANTIKORUPSI TERHADAP GENERASI ALPHA MENGGUNAKAN PENDEKATAN BELA NEGARA - Aji Lukman Ibrahim; Dian Khorenita Pratiwi; Suprima; Aditama Candra Kusuma; Ayu Diah Rahmani; Rindu Audrye (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
This community service uses the lecture, counseling, and discussion methods titled "Anti-Corruption Education Against Generation Alpha Using the State Defense Approach." The long-term goal of this service, the anti-corruption education program, is to be able to provide a sense of awareness and understanding of the notion of corruption, types of corruption, factors causing corruption, and prevention of corruption as a form of implementation of state defense that is adapted to the context of grade 5 school students. The specific target is the alpha generation, which is well educated regarding the understanding, types, causal factors, and prevention of corruption as well as the implementation of state defense. Kegiatan was carried out in the hall at Rawa Barat 05 State Elementary School, which had previously been coordinated with the principal, class teachers, and school stakeholder groups. The main purpose of this service is to implement the values of defending the state against the alpha generation in the spirit of anti-corruption in the future. This activity begins with a Pre test to determine how far the participants' knowledge is related to the theme, then education is given in accordance with the context of the 5th grade students, and the activity ends with a Post test.